Effect of Peanut (Arachis hypogaea L.) on Fasting Blood Glucose and HbA1c in Alloxan Induced Diabetic Male Rats - Akter, Fatema; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2015)
Background: Diabetes mellitus (DM) is a heterogeneous group of metabolic disorders with micro and macrovascular complications which are the major causes of morbidity and mortality in diabetic patients. Peanut due to its anti-oxidant property can reduce blood glucose level and may reduce the risk of diabetes. Objective: To observe the anti-diabetic effects of peanut (Arachis hypogaea L.) in alloxaninduced diabetic male rats. Method: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka in 2013. For this purpose, 15 wistar albino male rats, aged 90-120 days, weighing 160-200 g (initial body weight) were included in the experimental group (DG-A-P). Age and weight matched 20 wistar albino rats without peanut supplementation was taken as control and divided into (BC and DC-A) . All groups of animals received basal diet for 21 consecutive days. In addition to basal diet, animals of DC-A received alloxan intraperitoneally only on the first day of the study. Moreover, animals of DG-A-P also received peanut extract for 21 consecutive days. After 16 hours of fasting blood samples were collected from tail vein of all rats on day-1 and day- 3. After taking final body weight all the rats were sacrificed on 22nd day. Their pancreas was removed and weighed. To observe glycemic control serum blood glucose and blood HbA1c levels were measured by usual laboratory technique. ANOVA, independent t-test and paired t-test were used for statistical analysis. Result: The % change of body weight was significantly (p<0.001) lower in DC-A in comparison to that of BC. The weight of pancreas was significantly lower in DC-A (p<0.001) and DG-A-P (p<0.05) when compared to that BC, whereas this level was significantly higher (p<0.001) in DG-A-P than that of DC-A. The mean fasting blood glucose level on day-3 was significantly (p<0.001) higher in DC-A and DG-A-P in comparison to that of BC. Then this level was significantly (p<0.001) lower in DG-A-P in comparison to that of DC-A on day-22. Moreover, significantly higher levels of HbA1c were observed in DC-A (p<0.001) and DG-A-P (p<0.05) in comparison to those of BC. Again, significantly (p<0.001) lower level of blood HbA1c were observed in DG-A-P than those of DC-A. Conclusion: From this study, it can be concluded that peanut (Arachis hypogaea L.) has anti-diabetic effect by reducing fasting blood glucose, HbA1c levels. This anti-diabetic effect may be due to its high MUFA content and anti-oxidant property. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22796 Bangladesh Soc Physiol. 2014, December; 9(2): 48-53